Reverse Watson-Crick Petri nets - Mohamad Jan, Nurhidaya; Fong, Wan Heng; Sarmin, Nor Haniza; Turaev, Sherzod (2014)
A Watson-Crick Petri net is a model that relates between Watson-Crick automaton and a Petri net where the control unit of the Watson-Crick automaton is replaced by the Petri net. The language generated by a Watson-Crick Petri net can be determined either by using the class of labeling functions or the set of final markings. In this paper, another type of Watson-Crick Petri net known as reverse Watson-Crick Petri net is introduced. Two examples are given to illustrate this new concept.